Characterization of semiconductor SnO2 based heterojunction and its optical response properties - Ong, Chi Wai. (2010)
Pure SnO2 and MgySn1-yO2-x thin film on silicon and quartz have been fabricated using Sol-Gel deposition technique. PZT thin film on silicon have also been prepared and fabricated with the same method. High quality epitaxial SnO2 thin films have been fabricated using Laser Beam Molecular Epitaxy (LMBE) on different substrates such as Si(001), STO:Nb and STO(111). The characterization of Magnesium doping (p-type dopant) on SnO2 thin film has been investigated in details. The Mg doping level range will be of 10% to 25% to increase the band gap of the SnO2 thin film’s band gap. Hence band gap engineering such as simulation of experimental results using Material Studio, analysis of transmission and absorbance by UV/Vis spectrophotometer and characterization by Ellipsometry have been carried out to prove the significant behavior of MgySn1-yO2-x thin film according to the Mg doping level. The absorbance coefficient will be calculated and extracted to plot a graph against photon energy so as to execute extrapolation for the individual’s band gap values. The X-Ray Diffraction (XRD) peak results are obtained and compared with the Joint Committee on Powder Diffraction Standard data. Surface morphology study by Atomic Force Microscopy (AFM) has been carried on the Mg-doped SnO2 thin films to observe and compare between surface roughness and Mg doping level. Lastly, electrical characterization such as I-V characteristic has been carried out on SnO2/STO:Nb heterojunction. Turn on voltage and reverse saturation current would be analyzed to prove existence of diode characteristic.